Пізньоантичні пантікапейські розписні склепи - Зінько, О.О. (Археологія, 2003)
Статтю присвячено оглядові пізньоантичних склепів боспорського некрополя, розташованих на північному схилі гори Мітридат, виявлених та досліджених упродовж останніх років. Статья посвящена анализу исследованных автором позднеантичных пантикапейских расписных склепов. На основе проведенных исследований грунтовых склепов позднеантичного некрополя Пантикапея на северном склоне горы Митридат в г. Керчи сделан вывод о необходимости проведения широкомасштабных работ по изучению этих археологических объектов, а также об обязательном выполнении комплекса мероприятий по консервации древней живописи и входов в погребальные комплексы. The article deals with late ancient decorated burial vaults investigated by the author of this paper. According to the researches of the burial vaults which had been dug out in soil of the late ancient cemetery of Penticapeum on the northern slope of the mounting of Mithradates in the territory of the town of Kerch the author has made a conclusion to carry out necessary researches on a large scale for coming to know of these archaeological objects as well as to make a complex of measures on conservation of ancient painting and entrances into the burial complexes.